Chromaticity and Color Filters for Fresnel Microprism. - Antonov, E. E. (Інститут проблем реєстрації інформації НАН України, 2019)
The application of Fresnel microprisms always reduces the contrast and worsens the resolution of the formed optical images. During ophthalmologic diagnostics the microprisms affect the visual acuity of the patient which is decreasing depending on the contract of test chart optotypes. The main reason for reducing the contrast and for worsening the resolution of optical images when using prisms is the chromaticity of white light that occurs when the light rays of different wavelengths are refracting on the prism surfaces. Therefore, quantitative data on this effect and the search for ways to reduce it are necessary. A color light filters can be used to diminish the chromaticity, so the chromatic aberrations with light filters should be considered quantitatively. From this point a modified rigid Fresnel microprisms with protected relief developed at the Institute for Information Recording (Ukraine) were investigated. Comparative optical characteristics were calculated for microprisms with yellow-blue and green-blue filters. Experimental data on chromaticity aberrations were obtained using new electronic method for registering the resolution of test stroke images with and without filters. The influence of light filters on the visual images through Fresnel microprisms was registered. These data are necessary to distinguish the effect of prisms and filters in the total decrease of the contrast. The reasons for contrast decrease and image resolution diminishing with light filters are discussed for all of investigated ophthalmic microprisms.